Territoriality varies across elevation in a Hawaiian songbird. (28th December 2022) - Names, Gabrielle R; Hahn, Thomas P; Wingfield, John C; Hunt, Kathleen E
Abstract: Reproductive territoriality can be influenced by external and internal variables. Trade-offs between reproductive behaviors and other costly biological processes, such as immunity, exist across taxa, but the effects of novel diseases on these trade-offs remain poorly understood. Since the introduction of avian malaria to Hawaii in the early 1900s, low elevation Hawaii Amakihi ( Chlorodrepanis virens ) populations, which have undergone strong selection by the disease, have evolved increased malaria resilience. However, the effects of malaria selection on trade-offs between immunity and reproduction in Amakihi remain largely unknown. To begin exploring this relationship, we conducted simulated territorial intrusions on Amakihi at low elevation (where malaria selection has been stronger) and high elevation (where selection has been weaker) on Hawaii Island during the breeding season. We hypothesized that selection by avian malaria has favored greater investment in avian malaria resilience at the cost of reproductive behaviors. We predicted that low elevation Amakihi would be less territorial compared with high elevation Amakihi, while recognizing that variables other than disease pressures that may differ across elevation (e.g., competition, predation) could explain behavioral variation. Territoriality was reduced in low compared with high elevation Amakihi as measured by proximity and chases in response to the intrusion. Low elevation Amakihi generally flew less than high elevation individuals, although this relationship varied across the breeding season. Our correlational results demonstrate that territoriality is greater in high compared with low elevation Amakihi. Further investigations would help determine which factors differing across elevation underlie this variation in territoriality. Abstract : Physiological and environmental factors influence territorial behavior. In Hawaii, high and low elevation populations of the Hawaii Amakihi songbird experience differences in selection by avian malaria as well as other biotic and abiotic factors. Our correlational study revealed that territoriality was reduced in populations at low compared to high elevation. Our results provide the foundation for future studies to determine whether avian malaria selection, or other factors related to elevation, cause this variation in behavior.